The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-313x.2009.03826.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of apomictic and sexual ovules in the Boechera holboellii complex

Abstract: SUMMARYApomixis, a natural form of asexual seed production in plants, has evolved independently in various taxa, and represents an important potential technology for agriculture. The switch to apomixis is based on de-regulation of developmental pathways originally leading to sexual seed formation. Hybridization and polyploidy, both typical characteristics of asexual plants and animals, are mechanisms that could trigger de-regulation. Here we show that up-regulation of alleles in apomeiotic ovules is mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
115
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 68 publications
(112 reference statements)
5
115
0
1
Order By: Relevance
“…Whether any of these genes play a primary role during the initiation of apomixis, autonomous embryogenesis or endosperm development in wild apomicts is sometimes difficult to assess, since time-consuming functional analysis is often required in complex polyploid sexual and apomictic systems to determine their relevance. In some cases, results are promising, such as those from diposporous Boechera and aposporous Poa pratensis L., where SERK homologues were shown to be differentially expressed between sexual and apomictic ovules, specifically in the cells initiating apomixis Sharbel et al 2009). In other cases, results are not so promising, such as that of the Arabidopsis FERTILISATION INDEPENDENT ENDOSPERM (FIE) FISclass gene that represses endosperm development in the absence of fertilisation.…”
Section: Did Apomixis Arise Through Mutation Of Sexual Genes?mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether any of these genes play a primary role during the initiation of apomixis, autonomous embryogenesis or endosperm development in wild apomicts is sometimes difficult to assess, since time-consuming functional analysis is often required in complex polyploid sexual and apomictic systems to determine their relevance. In some cases, results are promising, such as those from diposporous Boechera and aposporous Poa pratensis L., where SERK homologues were shown to be differentially expressed between sexual and apomictic ovules, specifically in the cells initiating apomixis Sharbel et al 2009). In other cases, results are not so promising, such as that of the Arabidopsis FERTILISATION INDEPENDENT ENDOSPERM (FIE) FISclass gene that represses endosperm development in the absence of fertilisation.…”
Section: Did Apomixis Arise Through Mutation Of Sexual Genes?mentioning
confidence: 99%
“…Recent support also comes from a study of apomixis in Boechera where transcriptomic profiling was used to compare allele-specific gene expression in ovules from related sexual and apomictic plants (Sharbel et al 2009). The results from this study show that several genes conserved in sexual and apomictic Boechera species are heterochronously expressed in the apomicts, and that altered levels of expression in the apomict are linked to gene duplication and parent-of-origin effects.…”
Section: Interspecific Hybridisation May Lead To the Initiation Of Apmentioning
confidence: 99%
“…Intensive research on Arabidopsis mutants has sought a way to change sexual reproduction to apomictic reproduction (Ravi et al, 2008). Analysis of mRNA tags of apomictic and sexual ovules in the Boechera holboellii complex implicate polyploid gene dosage in the expression of asexual seed formation, and support hypotheses of deregulation of the sexual pathway (Sharbel et al, 2009). Physical mapping of the apospory-specific genomic region (ASGR) in two apomictic grasses, Pennisetum squamulatum and Cenchrus ciliaris, showed that the ASGR appears to be maintained as a haplotype even though its position in the genome can be variable (Goel et al, 2006), and genetic mapping of the ASGR in P. squamulatum using retrotransposon-based molecular markers is problematic (Huo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sharbel et al (2009) have elegantly overcome some of these confounding effects by comparing sexual and apomictic species of the genus Boechera. This genus, a relative of Arabidopsis, includes extremely rare diploid apomicts as well as diploid sexual species, allowing for comparisons between related species of the same ploidy.…”
mentioning
confidence: 99%
“…This genus, a relative of Arabidopsis, includes extremely rare diploid apomicts as well as diploid sexual species, allowing for comparisons between related species of the same ploidy. In that first analysis, the authors performed transcriptome profiling of microdissected ovules at the megaspore mother cell stage and found evidence for effects of heterochrony, genome duplication, and ancient hybridization events in apomictic gene expression (Sharbel et al, 2009). Now, Sharbel et al (pages 655-671) make use of the same genus to delve further in the role of heterochrony in promoting apomixis.…”
mentioning
confidence: 99%